Infiltração de água ao longo de uma transeção em solos construídos na área de mineração de carvão de Candiota-RS. - Guadagnin, Clístenes Antônio (2002)
The knowledgement of the water infiltration capacity and its relation to soil physical properties is of utmost importance to evaluate the soil degradation in mining areas and to propose alternatives to minimize its effects and keep a good soil and water quality. In order to extract the coal, thick layers of soil and rocks are removed, bringing a series of visual, topographic and physiographic disturbances. The reclamation of these areas, usually made with very large and heavy equipment, involves the replacement of the layers previously removed, composed of different geological materials, and the covering with a layer of topsoil, removed from pre-mined areas. This composes a man constructed soil (minesoil), which normally presents characteristics that are very different from the original soil, that makes the revegetation difficult, favoring, consequently, its degradation. In order to evaluate the variation of the water infiltration rate two different types of minesoils (SC1 and SC2) were selected and compared to a native soil located nearby, classified as an alfisol. The water infiltration rate was Evaluated along 117 m transect at 3.0 m intervals, during an average 7,5 h period, until constant measurement, using PVC cylinders with 0.1425 m internal xii diameter and 0.25 m height, inserted 0.05 m into the soil. The measurements were done using a graduated ruler fixed in the internal walls of the cylinder interior after the establishment of a hydraulic head of 0.09 m, maintained constant along the time. After the analysis of the results it was concluded that: (a) the minesoils water infiltration rate is low to medium and higher than the reference native soil, which is very low; (b) the variation of the water infiltration rate along the transect in the minesoils is very high, with extreme values ranging from very low to very high in the recently reclaimed soil (SC1) and from low to high in the older minesoil (SC2), while the variation in the native soil is lower and more homogeneous; (c) the low macroporosity did not allow to establish a direct relation between its magnitude and the water infiltration rate; (d) the spatial variability parameters of the water infiltration rate indicate a week spatial dependence, with a trend of the minesoils showing a periodic fluctuation of the semivariance values along the transect.